METHODOLOGICAL APPROACHES TO ASSESSING THE EFFICIENCY OF MANNED AND UNMANNED AVIATION MIXED GROUPS MANAGEMENT - BABYCH, ANATOLIY; LYASHCHENKO, RUSLAN; HEORGIEV, YURIY; PAYANOK, OLEKSANDR (Herald of Khmelnytskyi National University. Technical sciences, 2025)
A mixed aviation group of manned and unmanned aircraft is a complex organizational and technical system with heterogeneous elements, the properties of which have significant dynamics of changes, in accordance with the conditions of its functioning, which exist or are predicted. The heterogeneity of the elements of such a system in terms of their functional capabilities and the transience of the environment for the implementation of these capabilities cause certain difficulties in managing the system. At the same time, under the conditions of technical parity of competing (opposing) systems, it is the managerial aspects of organizing the functioning of these systems that can provide advantages over one another. The main task that the management system must solve during the preparation for combat operations of a heterogeneous military formation, in particular a mixed aviation group, is to ensure the purposeful work of all components of the system, in accordance with the intended goals, which determines the priority of applying the traditional concept of military management, namely the concept of centralized management. But in the course of group management directly during the performance of a combat mission, the concept of situational management takes priority, especially under the conditions of management during a massive air strike, when the situation often changes, and in some cases even becomes a crisis state. The feasibility of using a particular management model can be determined by assessing its effectiveness. That is why the paper presents the proposes methodological approaches to assessing the effectiveness of management of mixed aviation groups of manned and unmanned aircraft, which include methods for assessing the internal properties of the group management system and methods for assessing the reaction of the external environment to management influences during the implementation of the group's combat potential. Criteria for the effectiveness of the internal properties of the group management system are determined, namely, such as the efficiency of making management decisions and their quality. A method for calculating the efficiency indicator is proposed as the probability that the decision-making time will not exceed the time specified in the combat order (directive). The fact that the quality of management is a complex category is proven. The main factors that affect the quality of management decisions are identified, methods for their formalization and calculation are proposed. Approaches to calculating integral indicators of the quality and efficiency of the internal properties of the group management system are defined. As a criterion for the effectiveness of external management influence, the result of the implementation of the group's combat potential during the execution of tasks according to the plans of the operation (combat actions) of troops (forces) is proposed. The indicator of the effectiveness of management influence is proposed to be defined as the ratio of the lost combat potential of the group during the operation (period of combat actions) to the initial management potential, as a component of the general combat potential of the group. A model of the process of assessing the effectiveness of management of a mixed aviation group of manned and unmanned aviation is presented and substantiated.
Keywords: combat potential; losses of combat potential; management effectivenessmixed aviation group; management effectiveness criteria; management efficiency; initial management potential; environments for the implementation of combat potential; management system; management quality